Big data in pharmacy practice: current use, challenges, and the future - Ma C; Smith HW; Chu C; Juarez DT (Dove Medical Press, 2015)
Carolyn Ma, Helen Wong Smith, Cherie Chu, Deborah T JuarezDepartment of Pharmacy Practice, The Daniel K Inouye College of Pharmacy, University of Hawai'i at Hilo, Hilo, HI, USAAbstract: Pharmacy informatics is defined as the use and integration of data, information, knowledge, technology, and automation in the medication-use process for the purpose of improving health outcomes. The term “big data” has been coined and is often defined in three V's: volume, velocity, and variety. This paper describes three major areas in which pharmacy utilizes big data, including: 1) informed decision making (clinical pathways and clinical practice guidelines); 2) improved care delivery in health care settings such as hospitals and community pharmacy practice settings; and 3) quality performance measurement for the Centers for Medicare and Medicaid and medication management activities such as tracking medication adherence and medication reconciliation.Keywords: clinical pharmacy data base, pharmacy informatics, patient outcomes